PENENTUAN HARGA JUAL USAHA TANI SEMANGKA BIJI (CITRULUS VULGARIS) DI DESA SUMENGKO KECAMATAN WRINGIN ANOM KABUPATEN GRESIK - Rr. Nugrahini SW; Achmad Dadang DJ (UMSurabaya Publishing, 2006)
To Decide sale price of water melon cultivation can by break even point analysis. In this research, production breack even point at 282,43 Kg/ ha and production price break event point at 282,47 rupiah..To make raising income need increasing salesprice or increasing production volume water melon.